Manejo del paciente politraumatizado por accidente de tránsito atendido por el servicio ECU 911 de la ciudad de Loja en el periodo septiembre 2015 - febrero 2016. - Cabrera Cabrera, Carlos Alberto (2017)
The Polytrauma is the existence of multiple injuries in different body regions most frequently caused by traffic accidents it is carried out by a quantitative, descriptive, retrospective and transversal study whose objectives are to know the handling, arrival time, attention, transportation, gender and age group of patients. Polytrauma in traffic accidents are attended by the ECU 911 of Loja City. The information was obtained from the database of the ECU 911 Loja city; are register 565 patients attended during the period September 2015-February 2016. In the 100% (n=564) is done an airway appraisal, 4,07% (n=23) receiving assisted ventilation, 100% (n=553) control of the circulation is effected and in the 62,65% (n=354) is performed neurological appraisal The average time that an emergency person use in to arrive to the scene is of 0 to10 minutes in 69,38% (n=392), 39,65% (n=224) delay between 0 to 15 minutes in attendance in the incident scene and 37,88% (n=214) of patients they were transferred in a time of 0 to10 minutes; the age of the victims that present more frequently is between 21 to 30 years 31,33% (n=177),being more prevalent male gender 67.61% (n = 382) of cases. Keywords: Polytrauma, management, traffic accidents, transportation, gender.